Facilitative Effects of Embodied English Instruction in Chinese Children - Guan, Connie Qun; Meng, Wanjin (Frontiers in Psychology, 2022)
Research into the lexical quality of word representations suggests that building a strong sound, form, and meaning association is a crucial first step for vocabulary learning. For children who are learning a second language (L2), explicit instruction on word morphology is generally more focused on whole word, rather than sub-lexical, meaning. Though morphological training is emphasized in first language (L1) vocabulary instruction, it is unknown whether this training facilitates L2 word learning through sub-lexical support. To test this, we designed three experimental learning conditions investigating embodied morphological instruction [i.e., hand writing roots (HR), dragging roots (DR), gesturing roots (GR)] to compare against a control condition. One hundred students were randomly assigned to the four experimental groups. Pre- and post-tests examining knowledge of word meanings, forms, and sounds were administered. Results of mixed linear modeling revealed that three embodied morphological instruction on roots enhanced L2 vocabulary learning. Hand writing roots facilitated sound-meaning integration in all category-tasks for accessibility to word form and one task for word sound-form association. By contrast, GR facilitated meaning-based learning integration in two out of three category tasks for word form-meaning association. Chunking and DR facilitated meaning-based integration in one out of three category tasks for word form-meaning association. These results provide evidence that the underlying embodied morphological training mechanism contributes to L2 vocabulary learning during direct instruction. Future directions and implications are discussed.